The versatility of drama-based pedagogy and teacher training (Training and Practice : Journal of Educational Sciences, 2019)
In drama-based pedagogy, the insights of several sciences and arts interact with one another: art pedagogy, psychology, pedagogy, puppetry, acting, literature, music. Unfortunately, the approach of drama-based pedagogy is gaining less and less ground in today's educational practice. Those, however, who adopt it know that emotional-intellectual learning can be greatly facilitated by this method. The tool system of drama-based pedagogy helps the work of several educators, psychologists and trainers. It is well-known that we can talk about dramatic play activities in the usual sense from kindergarten age onwards. The common activities of children, led by the referee, promote self-knowledge, knowledge of each other and of the world, and serve personality formation. Every play is dramatic in its character, based on imitation of life situations and behaviour patterns. As Gavin Bolton puts it: from a pedagogical point of view, drama is a game that builds an imaginary world, involves the actors in it, makes them face real-life problems and conveys them thereby real knowledge and real experiences. The power of drama lies in the fact that it seems to be real action. Its thinking is embedded in action, and its goal is to create meaning by mediating between two contexts (Bolton, 1993).